The Development of Critical Management Studies in Spanish-speaking Latin American countries - Gantman, Ernesto R. (Política y Sociedad, 2016)
This article’s goal is to examine the development of critical management studies in the Spanish-speaking Latin American countries. I examine the production of the top five countries in terms of the production of scientific articles in business and management. (México, Argentina, Chile, Colombia and Venezuela.). The analysis is descriptive and seeks to identify the production of both conceptual and empirical knowledge in books and articles whose subject is related to the tradition of critical management studies. After a review of the relevant literature, it can be concluded that there is a certain level of production in the countries analyzed. In addition, it can be observed that, in some countries, the development of research framed within a critical perspective to management and organizations is not only carried out by researchers affiliated with business schools or faculties of economic sciences, but by those who work in academic units of other social sciences. To conclude, the article provides some reflection about the prospects for the development of CMS in the region.